Producción y comercialización de arroz en la ciudadela Nueva Esperanza del cantón Babahoyo - Diaz Villacis, Carlos Alberto (2021)
This research work consists of the description and analysis of the production and commercialization of rice in the New Hope citadel of the Babahoyo canton, this within the agricultural area of the Province of Los Ríos. The research was carried out in order to analyze all those aspects that influence the management of rice production and commercialization, considered essential for the better development of these activities. The analysis will help the agricultural association to design strategies aimed at improving those aspects in which there are deficiencies and in turn the application of a more efficient system that is currently available. The problem, on the other hand, arises from the concern of farmers to make a diagnosis of the current conditions of rice production and commercialization, this due to the concern of how this is done so far. In this case study, information was obtained from different sources, including documentation from the association, interviews, surveys, and other observations. Two fundamental variables are analyzed within this research, which are: (i) The process of rice production in all its stages together with the tools and resources used there, (ii) The process of rice commercialization and the knowledge that is available and later applied in this activity. All of the above favored the formulation of the conclusions, which are intended to inform the association of an expanded view of its current conditions.